Transformasi Budaya Dalam Al-Qur’an - Hakim, Nurul (IAIN Ponorogo, 2016)
Abstract: Everyone wants to have prosperity in their life. But in the point of fact, not all people are able to fulfill their fancy. As the result, such question rises